JERUSALEM'S HINTERLAND IN THE EIGHTH–SEVENTH CENTURIES BCE: TOWNS, VILLAGES, FARMSTEADS, AND ROYAL ESTATES. (December 2015) - Moyal, Yigal; Faust, Avraham
Abstract : Although many excavations and extensive surveys were carried out in the vicinity of Jerusalem, very few systematic attempts were made to analyse the Iron Age city's hinterland in its entirety. The present article summarises some of the general results of a detailed study of the area around Jerusalem, identifies the territories of the city's 'daughters' (satellite towns), and then focuses on two such units, in which settlement distribution was markedly different from other units: Moza and Ramat Raḥel. The article concludes that most of the territory around Jerusalem belonged to organically developed towns, the territories of which were densely dotted with villages and (mainly) farmsteads. Moza and Ramat Raḥel, however, functioned in the late Iron Age II (7th centurybce ) as royal estates (perhaps even as a palatial estate in the latter case), responsible for both the production and storage of surplus.